USING READER RESPONSE APPROACH TO GET ENGAGED IN ENGLISH TEXTS OF THE PAST - Nafisah, Nia (Universitas Pendidikan Indonesia, 2014)
Abstract: This study investigates the students’ interpretations of English literary texts produced in the heyday of British and American Literature –the Victorian Age and Modernism. The fact that the texts are so distant from the students’ time and cultural contexts often becomes the obstacles in understanding, in particular, canonized literary texts. Moreover, in EFL classes where students do not use English in daily basis, the problem is multifold. On the other hand, despite the advice to use texts that are more contextual and meaningful to EFL learners, it is unavoidable for EFL students majoring English literature to read some canonical texts. Although the use of canonical works may present ideological and political bias (see (Said, 1979) and (McCallum Stephen, 2011)), Lazar (2005) argues that literature, among others, opens access to cultural background, expands students’ language awareness and develops students’ interpretative abilities. Confronting with time and space so different from the students’ own, this study employing reader response theory and analyzes how these EFL students majoring English literature construct meaning from three texts they read and its effects towards their interpretative abilities. The data were collected through students’ responses, questionnaires and focus group discussions. Keywords: English literature, canonized literary texts, EFL contexts, reader response